Different faces of passion in the context of leadership - Kozłowski Rafał (Management, 2016)
The paper describes passion, which depending on the context, may motivate entrepreneurial leaders not only to found an organization, but also to grow and expand their ventures. It should also be noted that there is also the dark side of passion dominated by greed and hubris, which may result in counterproductive outcomes.